The Impact of a NordDRG-based System on the Behaviour of Swedish Hospitals, An empirical analysis of a prospective payment system based on diagnosis-related groups - Sönne,Nathalie (2019)
The aim of this study is to contribute to previous research on the use of Prospective Payment Systems (PPS) based on Diagnosis Related Groups (DRG) in Sweden with an extended evaluation of variation in the utilisation of the system on recent data. This study looks specifically at within county financing and the role the system has played on the performance and behaviour of Swedish hospitals in regards to the number of DRG-weights registered in inpatient and outpatient healthcare. The method used for the analysis is based on a higher dimension fixed effects model, taking into account time-, county-, and diagnosis fixed effects. The data covers the 21 Swedish counties for the time period 2005 - 2017. The dependent variable of interest is DRG-weights, which is analysed for inpatient care, outpatient care and the total effect of the two combined. Several robustness tests are also run. The empirical analysis lacks most statistical significance, but a trend suggests that there is a positive impact on outpatient care regarding the amount of DRG-weights registered. The results also indicate a negative impact on inpatient care and a weak negative combined effect on the full sample. This implies that the use of the NordDRG-system may have ambiguous impacts on hospital behaviour. This study suggests an indication of how the financing system influences hospital behaviours and potential changes in quality seen through unplanned readmission rates.
Keywords: Diagnosis Related Groups; Swedish healthcare; Healthcare financing; Inpatient Care; Outpatient Care